2015
DOI: 10.14440/bladder.2015.48
|View full text |Cite
|
Sign up to set email alerts
|

Clinical utilization patterns of alvimopan in a contemporary cohort of patients undergoing radical cystectomy

Abstract: OBJECTIVE:To evaluate the clinical utilization patterns and outcomes of alvimopan, a peripherally-acting µ-opioid receptor antagonist, after radical cystectomy (RC) and urinary diversion at a high-volume cancer center. PATIENTS AND METHODS:We retrospectively identified 130 consecutive patients who underwent RC and urinary diversion for bladder cancer at our institution from October 2013 to September 2014. Demographic, clinical, and postoperative outcomes were compared between patients who did and did not recei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It also should be noted that while a majority of the ERAS protocol initiatives implement each element simultaneously, individual element use and adherence is often not reported in the study. We have previously shown that after FDA approval of alvimopan, 13% of patients who were eligible did not receive it (11). This can be seen in the original alvimopan study as well, where only 83% of patients received the medication (12).…”
Section: Limitations Of Erasmentioning
confidence: 99%
“…It also should be noted that while a majority of the ERAS protocol initiatives implement each element simultaneously, individual element use and adherence is often not reported in the study. We have previously shown that after FDA approval of alvimopan, 13% of patients who were eligible did not receive it (11). This can be seen in the original alvimopan study as well, where only 83% of patients received the medication (12).…”
Section: Limitations Of Erasmentioning
confidence: 99%